Analysis of two CBP (cAMP-response-element-binding protein-binding protein) interacting sites in GRIP1 (glucocorticoid-receptor-interacting protein), and their importance for the function of GRIP1 - Huang, Shih-Ming (Portland Press Ltd., 2004)
The p160 co-activators, SRC1 (steroid receptor co-activator 1), GRIP1 (glucocorticoid-receptor-interacting protein 1) and ACTR (activator for thyroid hormone and retinoid receptors), have two ADs (activation domains), AD1 and AD2. AD1 is a binding site for the related co-activators, CBP (cAMP-response-element-binding protein-binding protein) and p300, whereas AD2 binds to another co-activator, co-activator-associated arginine methyltransferase 1 (CARM1). Here, we identified two CBP-interacting sites [amino acids 1075–1083 (site I) and 1095–1106 (site II)] in a so-called CBP-dependent transactivation domain (AD1; amino acids 1057–1109) of GRIP1. Site I was the major site for CBP-dependent AD1 transactivation activity of GRIP1 whereas, following the deletion of site II, full or partial transactivation activity was retained without the recruitment of CBP in yeast, HeLa, human embryonic kidney 293 and CV-1 cells. GRIP1 (with a deletion of site II) expressed stronger co-activator activity than that of wild-type GRIP1 in the TR (thyroid receptor) and the AR (androgen receptor), but not the ER (oestrogen receptor), systems in HeLa cells. We also demonstrated that these CBP-binding sites of GRIP1 are not the only functional domains for its AD1 function in TR, AR and ER systems in HeLa cells by the exogenous overexpression of one E1A mutant, which led to a lack of CBP-binding ability. Our results suggest that these two CBP-interacting sites in the GRIP AD1 domain not only determine its AD1 activity, but are also involved in its co-activator functions in some nuclear receptors.